Synthesis of Ag-Cu based epoxy polymer composite for electrical conductivity. (2021) - Arshad Javid, Muhamad; Sadaqat, Nazish; Rafique, Muhammad; Nabi, Ijaz ul; Nadeem, Khalid
Abstract: In this study bimetallic Ag-Cu alloy has been synthesized using chemical reduction method. Fabricated Ag-Cu nanoparticles were used as conductive filler and the epoxy resin as polymer to produce Ag-Cu epoxy composites. Conductive filler with different concentration (1 wt% 2 wt%, 3 wt%, 4 wt%, 5 wt% and 10 wt%) were added in epoxy resin to investigate the electrical properties of Ag-Cu based epoxy composites . XRD pattern of Ag-Cu alloy formed fcc phase with miller indices (0 0 2), (1 1 1) and (2 0 0). For surface morphology, scanning electron microscopy (SEM) was used to perceive structure of alloy based epoxy composites and EDX confirmed the Ag-Cu elements in samples. Surface and volume resistivity of epoxy-based composite was investigated by Mega Ohm Meter-1865. Electrical conductivity of the Ag-Cu based epoxy polymer composites was measured to enhance the flow of electron in dielectric property of epoxy resin with conductive material of Ag-Cu alloy for practical application and potential fabrication of numerous electronic devices such as electrical conductive adhesives as well as micro/nano electro-mechanical systems.